Structural basis for the formation of soy protein nanofibrils. Issue 11 (21st February 2019) - Josefsson, Leila; Cronhamn, Melker; Ekman, Malin; Widehammar, Hugo; Emmer, Åsa; Lendel, Christofer
Abstract : Identification of the peptide building blocks of soy protein nanofibrils provides new clues about the determinants of protein nanofibril morphology. Abstract : Amyloid-like protein nanofibrils (PNFs) can assemble from a range of different proteins including disease-associated proteins, functional amyloid proteins and several proteins for which the PNFs are neither related to disease nor function. We here examined the core building blocks of PNFs formed by soy proteins. Fibril formation at pH 2 and 90 °C is coupled to peptide hydrolysis which allows isolation of the PNF-forming peptides and identification of them by mass spectrometry. We found five peptides that constitute the main building blocks in soy PNFs, three of them from the protein β-conglycinin and two from the protein glycinin. The abilities of these peptides to form PNFs were addressed by amyloid prediction software and by PNF formation of the corresponding synthetic peptides. Analysis of the structural context in the native soy proteins revealed two structural motifs for the PNF-forming peptides: (i) so-called β-arches and (ii) helical segments involved in quaternary structure contacts. However, the results suggest that neither the native structural motifs nor the protein of origin defines the morphology of the PNFs formed from soy protein isolate.